The Role and Importance of Empowering Rural Communities for Rural Development in Afghanistan - Fayaz Gul Mazloum Yar; Mahboobullah Musadiq (Jurnal Syntax Admiration, 2024)
Empowerment in Afghanistan’s rural areas has the potential to significantly transform rural residents' knowledge, attitudes, and work practices. Empowerment is fundamental for achieving development, as progress without empowering marginalized Afghan communities is often deemed unattainable. Empowering rural communities can be understood as a process of enhancing individuals' capacities to utilize their autonomy and mobilize local resources in productive and innovative ways within their communities. Any community development initiative rooted in local resources should aim to reduce poverty in diverse rural settings. Therefore, to foster local development and advancement, it is imperative to focus on empowering these communities by harnessing their talents and capabilities and utilizing natural, social, and advanced technological resources. This approach paves the way for community flourishing and sustainable development. This study aims to formulate strategies for managing rural empowerment aligned with sustainable development. Using a qualitative content analysis of relevant sources, data were collected through document analysis. The research revisits past studies and theories, synthesizing them to introduce the background of empowerment while tracing the trajectory of research surrounding the necessity of empowerment with a sustainable rural development approach.